The SEEKING Drive and Its Fixation: A Neuro-Psycho-Evolutionary Approach to the Pathology of Addiction - Alcaro, Antonio; Brennan, Anthony; Conversi, David (Frontiers in Human Neuroscience, 2021)
Neuro-ethological studies conducted by Panksepp and his colleagues have provided an understanding of how the activity of the mesolimbic dopaminergic (ML DA) system leads to the emotional disposition to SEEK/Explore, which is involved in all appetitive motivated behavior and mental activity. In pathological addiction phenomena, this emotional disposition "fixes" itself on certain obsessive-compulsive habits, losing its versatility and its natural predisposition to spontaneous and unconditioned activation. Overall, the result is a consistent disinterest in everything that is not the object of addiction. From a neuro-psycho-evolutionary point of view, the predisposition to develop addictive behavior can be attributed to a loss of “functional autonomy” of the SEEKING/Explorative disposition. Indeed, as shown by animal and human studies, the tendency to be conditioned by situations and contexts that provide an immediate reward can be closely related to a deficit in the tonic endogenous activity of the ML DA-SEEKING system.